2016
DOI: 10.1371/journal.ppat.1005407
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Is Involved in IFN-α Production and TRAIL Expression by HIV-1-Exposed Plasmacytoid Dendritic Cells: Impact of the Crosstalk with NK Cells

Abstract: Plasmacytoid dendritic cells (pDCs) are innate sensors of viral infections and important mediators of antiviral innate immunity through their ability to produce large amounts of IFN-α. Moreover, Toll-like receptor 7 (TLR7) and 9 (TLR9) ligands, such as HIV and CpG respectively, turn pDCs into TRAIL-expressing killer pDCs able to lyse HIV-infected CD4+ T cells. NK cells can regulate antiviral immunity by modulating pDC functions, and pDC production of IFN-α as well as cell–cell contact is required to promote NK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 100 publications
3
13
0
Order By: Relevance
“…Cell free virus are taken up by pDCs through endocytosis mediated by envelope–CD4 interaction ( 23 , 24 ), while cell-associated virus enter pDCs by fusion or endocytosis ( 14 ). Although cell-associated viruses are at a high level in vivo , they are a less potent inducer of IFN-I than cell free virus ( 25 ). One of the possible reasons is that most of cell-associated viruses are defective viruses which are not able to induce effective immune responses.…”
Section: The Induction Of Ifn-i In the Process Of Hiv-1 Infectionmentioning
confidence: 99%
“…Cell free virus are taken up by pDCs through endocytosis mediated by envelope–CD4 interaction ( 23 , 24 ), while cell-associated virus enter pDCs by fusion or endocytosis ( 14 ). Although cell-associated viruses are at a high level in vivo , they are a less potent inducer of IFN-I than cell free virus ( 25 ). One of the possible reasons is that most of cell-associated viruses are defective viruses which are not able to induce effective immune responses.…”
Section: The Induction Of Ifn-i In the Process Of Hiv-1 Infectionmentioning
confidence: 99%
“…From a functional perspective, levels of IFN- secretion in pDC from controllers and HIV-1-negative individuals are not noticeably different, but clearly exceed those of HIV progressors, which downregulate the CD4 receptor and may become refractory to antigenic stimulation due to elevated plasma levels of IFN- and other pro-inflammatory cytokines [53, 54]. In line with these observations, three-dimensional microscopic imaging indicated that pDCs from controllers and healthy donors, but not from progressors, contained high levels of intracellular TRAIL that is recycled to the membrane after HIV exposure and can induce apoptosis in virally infected CD4 T cells in a process that was recently described to be regulated by the alarmin HMGB1 [53, 55]. In contrast, pDCs from viremic patients appeared to constitutively express TRAIL on the cell surface without any viral stimulation, which may contribute to unspecific induction of cell death in CD4 T cells and may by this mechanism aggravate CD4 T cell losses and cellular immune deficiency.…”
Section: Introductionmentioning
confidence: 84%
“…Our results show that over a period of 9-months, ART partially restored pDC numbers, however, the immunogenic phenotype of pDCs was not significantly restored. While impairment of single pDC functions was demonstrated in several reports [ 15 , 18 , 19 , 30 , 31 ], in the present study we analyzed a complex dysfunction of pDC covering expression of the MHC class II ligand, the high affinity HIV-1 receptor CD4, the regulatory receptor BDCA-2, the Fcγ receptor CD32, the pDC dysfunction marker TIM-3, and the marker of killer pDC, TRAIL.…”
Section: Discussionmentioning
confidence: 99%